Isophthalate-Hydrazone 2D Zinc-Organic Framework: Crystal Structure, Selective Adsorption, and Tuning of Mechanochemical Synthetic Conditions - Roztocki, Kornel; Jedrzejowski, Damian; Hodorowicz, Maciej; Senkovska, Irena; Kaskel, Stefan; Matoga, Dariusz (Inorganic Chemistry, 2016)
A new layered mixed-linker metal-organic framework [Zn2(iso)2(pcih)2]n (MOF) built from isophthalate ions (iso2-) and 4-pyridinecarbaldehyde isonicotinoyl hydrazone (pcih) was prepared using both solution and mechanochemical methods. By use of the latter, the 2D MOF is obtained either in a one-mortar three-component grinding or on the way of a two-step mechanosynthesis. Tuning of mechanochemical synthetic conditions allowed us to identify both necessary and favorable factors for the solid-state formation of the MOF. Single-crystal X-ray diffraction reveals the presence of interdigitated layers in the ABAB arrangement and interlayer 0D cavities filled with guest molecules. Upon thermal activation, the dynamic framework exhibits stepwise and selective adsorption of CO2 over N2 as well as high-pressure H2 adsorption reaching maximum excess of 1.15 wt% at 77 K. The mechanochemical synthetic protocol is expanded to a few other interdigitated structures.
CRIS-Team Scopus Importer:2023-03-20